Ultra-high drug loading improves nanoparticle efficacy against peritoneal mesothelioma. (June 2022) - Sabatelle, Robert C.; Liu, Rong; Hung, Yin P.; Bressler, Eric; Neal, Eliza J.; Martin, Andrew; Ekladious, Iriny; Grinstaff, Mark W.; Colson, Yolonda L.
Abstract: Peritoneal mesothelioma is an aggressive disease with a median survival of under three years, due to a lack of effective treatment options. Mesothelioma is traditionally considered a "chemoresistant" tumor; however, low intratumoral drug levels coupled with the inability to administer high systemic doses suggests that therapeutic resistance may be due to poor drug delivery rather than inherent biology. While patient survival may improve with repetitive local intraperitoneal infusions of chemotherapy throughout the perioperative period, these regimens carry associated toxicities and significant peri-operative morbidity. To circumvent these issues, we describe ultra-high drug loaded nanoparticles (NPs) composed of a unique poly(1, 2-glycerol carbonate)- graft -succinate-paclitaxel (PGC-PTX + PTX) conjugate. PGC-PTX + PTX NPs are cytotoxic, localize to tumor in vivo, and improve survival in a murine model of human peritoneal mesothelioma after a single intraperitoneal (IP) injection compared to multiple weekly doses of the clinically utilized formulation PTX-C/E. Given their unique pharmacokinetics, a second intraperitoneal dose of PGC-PTX + PTX NPs one month later more than doubles the overall survival compared to the clinical control (122 versus 58 days). These results validate the clinical potential of prolonged local paclitaxel to treat intracavitary malignancies such as mesothelioma using a tailored polymer-mediated nanoparticle formulation.